The role of tumor-associated macrophages and soluble mediators in pulmonary metastatic melanoma - Xiong, Kaifen; Qi, Min; Stoeger, Tobias; Zhang, Jianglin; Chen, Shanze (Frontiers in Immunology, 2022)
Skin malignant melanoma is a highly aggressive skin tumor, which is also a major cause of skin cancer-related mortality. It can spread from a relatively small primary tumor and metastasize to multiple locations, including lymph nodes, lungs, liver, bone, and brain, however, metastatic melanoma is the main cause of its high mortality. Among all organs, the lung is one of the most common distant metastatic sites of melanoma, and the mortality rate of melanoma lung metastasis is also very high. Elucidating the relevant mechanism of cutaneous melanoma lung metastasis not only helps to provide possible explanations for disease pathogenesis but may also help to provide potential new therapeutic targets for the treatment of melanoma lung metastases. Increasing evidence suggests that tumor-associated macrophages (TAMs) play an important regulatory role in the migration and metastasis of various malignant tumors. Tumor-targeted therapy, targeting tumor-associated macrophages is thus attracting attention, particularly for advanced tumors and metastatic tumors. However, the relevant role of tumor-associated macrophages in cutaneous melanoma lung metastasis is still unclear. This review will present an overview of the origin classification, polarization, and recruitment of tumor-associated macrophages and their possible role in lung metastasis of skin malignant melanoma, as well as it’s their role in cell-targeted therapy. This review particularly aims to provide insight into mechanisms and potential therapeutic targets to readers, interested in pulmonary metastasis melanoma.